Soil Remediation Practices for Hydrocarbon and Heavy Metal Reclamation in Mining Polluted Soils - Nigel Makombe; Reginald Dennis Gwisai (The Scientific World Journal)
The study assessed the pollution, biodegradation rates, and phytoaccumulation of total petroleum hydrocarbons (TPHs), Lead (Pb), Cadmium (Cd), and Arsenic (As) in soils in the wet and dry seasons and compared them with set standards. Ten samples of 1kg each were randomly collected and mixed for each site that is the upgradient control site (10m2 strata design) and the downgradient contaminated site (16m2 strata design) to make a composite sample for each site. Three representative samples were collected and replicated for four months on both sites. Pot experiments were run with the same concentration levels of TPHs, Pb, As, and Cd. Each pot experiment was also replicated four times for tobacco compost, chicken droppings, Brassica juncea, and the control. Inductive Coupled Spectrometry, SPSS, ANOVA, t-test, normality, and post hoc tests were carried out for analysis. TPHs, Pb, As, and Cd concentrations were significantly higher (p<0.05) than the limits (MHSPEN and USEPA). TPHs and heavy metals had the highest concentration levels in the soil at the selected site in the following order: TPHs>Pb>Cd>As. Bioremediation in a controlled experiment revealed that Chicken Droppings and Brassica juncea were effective in reclaiming TPHs, As, and Cd while Tobacco Compost was effective in reclaiming Pb. The highest mean concentrations of Pb, As, and Cd were found in Brassica juncea in the following increasing order: roots, stem, and leaves, respectively.